PENGUATAN KECERDASAN DIGITAL SEBAGAI FONDASI REMAJA KREATIF DAN KRITIS BERMEDIA SOSIAL - Murdani, Andika; Wijayati, Hasna; Haqqi, Halifa (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Technological advancements have brought teenagers closer to social media. However, massive exposure to social media without adequate digital intelligence, can lead to various problems, such as the rampant spread of hoaxes, hate speech, propaganda, and radicalized content. This has the potential to affect the way teenagers think and behave. This condition was experienced by teenagers in Karangwuni Village, Sukoharjo Regency, as partners of this activity. Based on the situation analysis, it was found that the low digital literacy among teenagers resulted in a lack of critical awareness in responding to information circulating on social media. This program aims to strengthen digital intelligence as a foundation for teenagers to be able to think creatively and critically in social media. The methods used was socialization, focus group discussions, and mentoring to improve participants' understanding and skills in filtering information, avoiding the negative impacts of social media, and optimizing digital media for self-development. The results showed participants' understanding increase about digital intelligence, social media ethics, and critical strategies in dealing with information in the digital world. In addition, the implementation of this understanding is reflected in changes in participants' attitudes and behaviors in utilizing social media more responsibly and productively. These findings indicate that strengthening digital intelligence can be a key factor in shaping a young generation that is not only adaptive to technological developments, but also able to use social media creatively and critically